Study of the effect of nitrogen-fxing cyanobacteria on the growth rate of the Strawberry Sunrise T-4 strawberry variety (Eurasian Journal of Ecology, 2020)
The article presents the results of the study of nitrogenase activity of five strains of cyanobacteriafrom the collection of phototrophic microorganisms of Al-Farabi Kazakh National University and their effect on the growth of strawberries. Nitrogen-fixing cyanobacteria were studied by strains Anabaena variabilis R-I-5, Anabaena sp. 7912, Anabaena sp. Z-1, Nostoc calsicola RI-3, Nostoc sp. S-2, and accordingto the results obtained high activity of nitrogenase in the strain Anabaena variabilis R-I-5. In the studyof the effect of cells of different concentrations of the strain Anabaena variabilis R-I-5 on the growth ofstrawberry Strawberry Sunrise T-4, it was found that its suspension of 24x106 cells/ml and 48x106 cell/ml had a positive effect on strawberry growth. In addition, an increase in the number of strawberry rootswas observed in the suspension of cyanobacterial biomass 24x106 cell/ml. An increase in the number ofstrawberry leaves, root length, stem height and a significantly higher yield of dry biomass of strawberrieswere observed in the suspension of the study in the amount of 48x106 cell/ml. The optimal cell count ofthe nitrogen-fixing cyanobacterium Anabaena variabilis R-I-5 suspension, which has a positive effect onthe growth of strawberry plants, was 48x106 cell/ml. The obtained results allow to use the nitrogen fixingstrain Anabaena variabilis R-I-5 for obtaining biological products in agrobiotechnology.Key words: Nitrogen-fixing cyanobacteria strains, grow of Strawberry Sunrise T-4 variety, molecularnitrogen absorption in air.